RTF TRANSFORM PROPERTIES - Rybin, O. I.; Natalenko, S. S.; Nizhebetska, U. H. (Radio Electronics, Computer Science, Control, 2010)
Precision of discrete RTF (Root domain Transfer Function) and Fourier transform is compared using the differentiation and integration operations. Expedience of using nonminimum difference formulae of differentiation in the RTF transform is stated.